A Nanomule Peptide Carrier Delivers siRNA Across the Intact Blood-Brain Barrier to Attenuate Ischemic Stroke - Eyford, Brett A.; Singh, Chaahat S. B.; Abraham, Thomas; Munro, Lonna; Choi, Kyung Bok; Hill, Tracy; Hildebrandt, Rhonda; Welch, Ian; Vitalis, Timothy Z.; Gabathuler, Reinhard; Gordon, Jacob A.; Adomat, Hans; et al. (Frontiers in Molecular Biosciences, 2021)
The blood-brain barrier (BBB) hinders the distribution of therapeutics intended for treatment of neuroinflammation (NI) of the central nervous system. A twelve-amino acid peptide that transcytoses the BBB, termed MTfp, was chemically conjugated to siRNA to create a novel peptide-oligonucleotide conjugate (POC), directed to downregulate NOX4, a gene thought responsible for oxidative stress in ischemic stroke. The MTfp-NOX4 POC has the ability to cross the intact BBB and knockdown NOX4 expression in the brain. Following induction of ischemic stroke, animals pretreated with the POC exhibited significantly smaller infarcts; accompanied by increased protection against neurological deterioration and improved recovery. The data demonstrates that the MTfp can act as a nanomule to facilitate BBB transcytosis of siRNAs; where the NOX-4 specific siRNA moiety can elicit effective therapeutic knockdown of a gene responsible for oxidative stress in the central nervous system. This study is the first to conclusively demonstrate both siRNA-carrier delivery and therapeutic efficacy in any CNS disease model where the BBB remains intact and thus offers new avenues for potential treatments of oxidative stress underlying neuroinflammation in variety of neuropathologies that are currently refractory to existing therapies.